The Effect of Enzymatic Alcoholysis on the Physicochemical Properties of Commercial Cocoa Butter Substitutes - Nazaruddin, R.; Zakiyan, S. Nurul i; Mamot, S. (Pakistan Journal of Nutrition, 2011)
The need for low-calorie fats has increased because of recent changes in consumers’ concerns about leading healthier lifestyles. Three types of commercial Cocoa Butter Substitutes (CBSs) were studied for use as substrates in the production of low-calorie structured lipids. Mixtures of commercial CBSs, ethanol and medium-chain fatty acids in a molar ratio of 1:2:1 were incubated in a water bath at 50oC for 24 h at 250 rpm, using 10% immobilized lipase as a catalyst. The following physicochemical properties were determined before and after enzymatic alcoholysis: the Solid Fat Content (SFC), the slip melting point, the iodine value, the free fatty acid content, the thermal behavior and the fatty acid composition. Hisomel CBSs was chosen as a substrate for further analysis because of its sharp melting profile between room temperature (25oC) and body temperature (37.5oC). At room temperature, the SFC of Hisomel was 60.56% and after the reaction with either caprylic or capric acid, it became 12.50% and 14.26%, respectively, which was the highest value among other CBS sample. Furthermore, Hisomel also had samilar fatty acid profile with cocoa butter before the enzymatic alcoholysis, which was 31.13% palmitic acid, 50.05% stearic acid and 18.80% oleic acid.